Effect Of Rambusa Fruit Extract (Passiflora Foetida) On The Growth Of Streptococcus Pyogenes Bacteria - Gede Vito Chandra Pramana; Nugroho Eko Wirawan Budianto (Universitas Wijaya Kusuma Surabaya, 2024)
Streptococcus pyogenes is a bacteria that can attack the epidermis and upper respiratory tract of humans, such as pharyngitis and impetigo. The rambusa plant (Passiflora foetida L) is famous for containing larvicide bioactive compounds. It also contains alkaloids, tannins, coumarins, procyanidins, triterpenoids, flavonoids, citric acid, acetogens, polyphenols, and saponins. A minority of individuals continue to employ this herb sporadically as an antibacterial agent. Intrigued by this phenomenon, the researchers set out to examine the effect of rambusa fruit (Passiflora foetida) administration on the Streptococcus pyogenes bacterium development inhibitory zone. This research uses Only Post Test Control Group Design, exclusively experimental. The population for this study was Streptococcus pyogenes bacteria obtained from the microbiology laboratory of the Faculty of Medicine, Wijaya Kusuma University, Surabaya. There were 24 samples in this study, with four repetitions per sample and consisting of 6 groups, including a treatment group with 4 subgroups (10%, 20%, 40%, and 80%), as well as two control groups. The Mann-Whitney U test showed that a concentration of 80% in the Passiflora foetida fruit extract treatment group resulted in an inhibitory zone diameter of 8.5 mm, which was statistically significant (P<0.05). The conclusion is that administration of rambusa fruit extract (Passiflora foetida) can inhibit bacterial growth of Streptococcus pyogenes, with the average highest inhibitory zone diameter being 8.5 mm